2013
DOI: 10.11002/kjfp.2013.20.4.510
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and antimicrobial activities of black Doraji (Platycodon grandiflorum)

Abstract: This study was conducted to investigate the antioxidant and antimicrobial activities of the hot-water and methanol extracts of raw and black Doraji to increase its utilization. In order to prepare the black Doraji, it was steamed for 15 days at a temperature of 60℃ and then it was dried at a temperature of 30℃ for 3 hr. The methanol extract from the black Doraji (BM) contained the highest levels of total polyphenols among the extracts, and the total polyphenol content of the extract from a black Doraji was hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…Lee et al ( 46 ) investigated the antioxidant and antimicrobial activities of hot-water and methanol extracts of raw and black PG. The antimicrobial activities of PG extracts were studied against bronchus disease bacteria (i.e., Mycobacterium sp., Staphylococcus aureus , Klebsiella pneumoniae , Corynebacterium diphtheriae , and Streptococcus pyogenes ) and food poisoning bacteria (i.e., Escherichia coli O157:H7 and Bacillus cereus ).…”
Section: Biological Activities Of Platycosidesmentioning
confidence: 99%
“…Lee et al ( 46 ) investigated the antioxidant and antimicrobial activities of hot-water and methanol extracts of raw and black PG. The antimicrobial activities of PG extracts were studied against bronchus disease bacteria (i.e., Mycobacterium sp., Staphylococcus aureus , Klebsiella pneumoniae , Corynebacterium diphtheriae , and Streptococcus pyogenes ) and food poisoning bacteria (i.e., Escherichia coli O157:H7 and Bacillus cereus ).…”
Section: Biological Activities Of Platycosidesmentioning
confidence: 99%
“…Antioxidant activity was measured by 2,2′-Azinobis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radical scavenging activity, α-diphenyl-β-picrylhydrazyl (DPPH) radical scavenging activity, and superoxide dismutase (SOD) activity as follows. ABTS radical scavenging activity was determined as described by Lee et al [ 27 ], with some modifications. The ABTS solution (1 mL) was mixed with 3 mL LAB samples and reacted for six minutes.…”
Section: Methodsmentioning
confidence: 99%
“…It has also been reported that the antibacterial effect of vinegar is due to the presence of organic acids, such as acetic acid and lactic acid. Moreover, bellflower roots are also known to contain several phenolic compounds, such as flavonoids, polyphenols, and saponins (e.g., platycodin) [32]. According to Medina et al [33], compared with aqueous extracts of wine, olive oil, and other beverages, vinegar has the strongest inhibitory effect against all tested pathogens.…”
Section: Antibacterial Activitymentioning
confidence: 99%